APPLICATIONS HOW TO OVERCOME THE PROBLEM SKIN AND BEAUTY THROUGH TRADITIONAL TREATMENT USING VISUAL BASIC 6.0 PROGRAMMING LANGUAGES - Binsar Daud; Elly Agustina. J, Skom, MMSI (Jurnal Sistem Informasi, 2006)
Many problems experienced by the public, especially the problem of disease and more particularly the problem of skin diseases. The problem is needed an expert / expert in that field. Time, money, and laziness of society to call the experts in overcoming these problems. Therefore the author made an application of traditional medicine, and the more specific issues related to skin problems because the skin is a light matter that the public / people are reluctant to seek expert skin. Applications that used to use Visual Basic 6.0, the reason being generated capacity is not too large, and shaped the visual because it is easier user.